Risk factors of the faiture of vaginal delivery after previous Cesarean section history. - Heru Pradjatmo Heru Pradjatmo (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2004)
Objective: To know factors influencing the success rate of vaginal delivery after previous Cesarean section history.Methods: Historical cohortSetting: Sardjito General Hospital YogyakartaParticipants: Women who delivered her child in Sardjito General Hospital between the year 1997 to 2001, and had previous Cesarean section history. Their delivery would be vaginally or recesarean section. The factors which were predicted affect the success of the vaginal delivery will be analyzed. The significance level of Odd Ratio was determined by logistic regression analysis.Results: There were 275 pregnant women with previous Cesarean section history reviewed, 110 (40%) patients successfully delivered the fetus vaginally and 165 (60%) patients unsuccessfully delivered the fetus vaginally and were undergone Cesarean section. Several factors that might influence the success of vaginal delivery were analyzed: place (OR =0.97; CI 0.58-1.65), age of the mother (OR =0.74; CI 0.431.29), mother body length (OR =1.15; CI 0.66-2.0), education of the mother (OR =1.41; CI 0.74-2.69), pregnancy interval (OR =0.83; CI 0.47-1.461, number of antenatal care (OR =4.40; CI 0.45-35.85), gestational age (OR =0.52; CI 0.24-1.12), fetal presentation (OR =0.61; CI 0.24-1.57), fetal body weight (OR =0.43; CI 0.21-0.89), history of vaginal delivery (OR =0.86; CI 0.51-1.43).Conclusions: It seems that only fetal body weight had significant influence to the success of the vaginal delivery after previous Caesarean section history. Anyhow, this result is appropriate to encourage a possible trial of vaginal delivery in almost all patients with a previous low-segment Caesarean section.Key words: Caesarean Section History, trial vaginal delivery, re-Caesarean Section